The Agile Management Paradigm in Quality-Based Curriculum Development in Integrated Islamic Schools - Kholil Bisyri; Siti Aimah (Journal of Educational Management Research, 2026)
The purpose of this study is to examine the application of the Agile Management paradigm in quality-based curriculum development, with particular attention to how adaptive, collaborative, and iterative principles enhance curriculum relevance and educational quality holistically. This study employs a qualitative approach using a case study design. Data were collected through semi-structured interviews, participatory observation, and document analysis involving key educational stakeholders, and were analyzed thematically through open, axial, and selective coding. The findings indicate that Agile Management contributes significantly to curriculum flexibility, stakeholder engagement, and continuous improvement. Adaptive practices enable curriculum adjustments aligned with students’ needs, collaborative processes strengthen shared ownership among stakeholders, and iterative cycles support ongoing refinement and integration of learning innovations. These results demonstrate that Agile-based curriculum management fosters a responsive and sustainable educational framework. The study implies that integrating Agile Management principles into curriculum governance can strengthen quality assurance systems, support contextualized learning, and enhance institutional capacity for continuous improvement in integrated Islamic education.